Hospice Social Workers: The Personal Death Experience. - James Power; Amelia Crane; Miranda Booker (Journal of Social Work Education and Practice, 2023)
Hospice social workers deal with death and dying on a routine basis. What happens when hospice social workers experience a personal death? This is a question which is not often raised. This study explored how social workers make meaning of personal deaths given their background in hospice care. These hospice social workers shared their early exposure to death within their families as important life events. These hospice social workers related the beneficial nature of their profession when dealing with a personal death. They saw their training as a “tool box” when dealing with a personal death. Their families often turned to them for advice and guidance. They have both professional and personal “hats” to wear. The hospice social workers conveyed the importance of support from co-workers during the grieving process. Furthermore, the organizational culture of their hospice employers impacted their ability to deal with their own personal loss.